2016
DOI: 10.3390/catal6060087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Support and Synthetic Procedure for Sol-Immobilized Au Nanoparticles

Abstract: Abstract:New gold catalysts supported on CeO 2 , ZrO 2 and TiO 2 were synthesized by two different techniques: deposition-precipitation and colloidal method. The role of the surfactant (PVA, PVP, THPC) was also investigated. The catalysts were tested in the oxidation of glucose to gluconic acid, in aqueous environment and under mild conditions (60˝C and atmospheric pressure). TEM and SEM analyses have shown that the small size of gold nanoparticles is a necessary condition, but not sufficient for a good conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…An interesting compound that can be used to improve the properties of ceria support is lanthanum. It could improve the thermal stability of the support and at the same time increase the oxygen vacancies, modifying ceria redox and structural properties [56,57]. Moreover, as mentioned above, it is possible that lanthanum oxide, being basic, improves the absorption of CO 2 and its interaction with the catalyst.…”
Section: Of 16mentioning
confidence: 99%
“…An interesting compound that can be used to improve the properties of ceria support is lanthanum. It could improve the thermal stability of the support and at the same time increase the oxygen vacancies, modifying ceria redox and structural properties [56,57]. Moreover, as mentioned above, it is possible that lanthanum oxide, being basic, improves the absorption of CO 2 and its interaction with the catalyst.…”
Section: Of 16mentioning
confidence: 99%
“…Their results indicated that SiO2-supported Au that featured large particles was more active during the liquid phase reaction, which indicated that the high dispersion and nature of the support were more important than the particle size. Signoretto et al [71] prepared CeO2-, TiO2-, and ZrO2-supported Au catalysts (Table 1, #22, 23, and 24, respectively) and demonstrated that the CeO2-supported Au catalyst was the most active of the three analyzed catalyst owing to its Au NPs being the smallest. In addition, CeO2 could store and deliver O2 to change the oxidation state from 3+ to 4+ [71].…”
Section: Metal Oxide-supported Au Catalystsmentioning
confidence: 99%
“…Signoretto et al [71] prepared CeO2-, TiO2-, and ZrO2-supported Au catalysts (Table 1, #22, 23, and 24, respectively) and demonstrated that the CeO2-supported Au catalyst was the most active of the three analyzed catalyst owing to its Au NPs being the smallest. In addition, CeO2 could store and deliver O2 to change the oxidation state from 3+ to 4+ [71]. Au/TiO2 did not present catalytic activity owing to the metal agglomerates.…”
Section: Metal Oxide-supported Au Catalystsmentioning
confidence: 99%
“…The use of the organophosphorus salt tetrakis-(hydroxymethyl)phosphonium chloride (THPC) and its double role as stabilizing and reducing ligand, enabled an easy and versatile procedure to generate different type of noble-metal nanocrystals in conventional laboratory-scale batch reactors with 15 mL (1 mM) production scale. Afterwards, the synthesis procedure of noble metal NPs based on the double role of THPC has been successfully adopted in the production of various types of catalysts [21][22][23][24][25][26][27][28] . Although the previously reported results using THPC 20,29 were well adopted and were very promising to produce a variety of stable noble metal NPs with an exquisite size control, there are several issues that still should be improved: a) The production throughput is limited due to the long synthesis-time required (i.e., 96h); b) A reproducible, efficient and easily scalable procedure should be designed; c) NPs should be homogeneously supported in order to be applied in any heterogeneous catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%